Kibbutz Mothering in Transition: Bringing the Children Home - Peled, Nancy (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
My generation of mothers on Kibbutz Hazorea is in the unique situation of having mothered in two contexts: the “normal” way and the kibbutz way, which involved communal sleeping arrangements for children. This system lasted until the 1991 Gulf War when the children moved home, leading to the de-facto end of collective education for kibbutz children. I investigate how the role of “mother” evolved in this transition from communal childrearing to full-parental responsibility as well as how the mothers felt about the transition. I also address what effect, if any, their own upbringing had on their experiences. I interviewed kibbutz mothers raised in communal education; kibbutz mothers who joined the kibbutz as adults; and a subgroup of women who worked as childcare givers (metaplot). Investigating the experience of mothering on kibbutz in its transition from collective childrearing to the traditional framework of the nuclear family can illuminate alternative perspectives of this unique kibbutz experience, focusing on whether and/or how the kibbutz prescription of mothering defined “mother” for the women who lived it.